2013
DOI: 10.3389/fphys.2013.00344
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of membrane associated proteins in the choroid plexus epithelium from normal and slc4a10 knockout mice

Abstract: The choroid plexus epithelium (CPE) has served as a model-epithelium for cell polarization and transport studies and plays a crucial role for cerebrospinal fluid (CSF) production. The normal luminal membrane expression of Na+,K+-ATPase, aquaporin-1 and Na+/H+ exchanger 1 in the choroid plexus is severely affected by deletion of the slc4a10 gene that encodes the bicarbonate transporting protein Ncbe/NBCn2. The causes for these deviations from normal epithelial polarization and redistribution following specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…Genetic disruption of Ncbe resulted in a reduced volume of the brain ventricles, which was paralleled by the decrease in the Na + -dependent HCO 3 − uptake in CPECs [12]. We reported that the abundance and membrane targeting of various proteins in the CPECs were affected by Ncbe ko [13,15]. Here, we provide a comprehensive overview of the observed cellular differences within the CP following Ncbe deletion.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Genetic disruption of Ncbe resulted in a reduced volume of the brain ventricles, which was paralleled by the decrease in the Na + -dependent HCO 3 − uptake in CPECs [12]. We reported that the abundance and membrane targeting of various proteins in the CPECs were affected by Ncbe ko [13,15]. Here, we provide a comprehensive overview of the observed cellular differences within the CP following Ncbe deletion.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, two of the most prominent luminal membrane proteins in CSF secretion were affected by the genetic slc4a10 disruption; we found reduced expression levels of the Na + ,K + -ATPase and the AQP1 to approximately 20% in the Ncbe ko mice, as compared to Ncbe wt mice [13]. The CPECs also displayed inversed localization of the Na + /H + exchanger NHE1 from the luminal side to the basolateral side in Ncbe ko [14] and further changes in cell polarity, cell contact and anchoring proteins [15]. Many of these changes would be consistent with a reduction of cellular secretory capacity.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Semiquantitative analysis of immunofluorescence images were performed as described previously (Christensen et al . ).…”
Section: Methodsmentioning
confidence: 97%